2016
DOI: 10.1186/s41200-016-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Colonization record of Isognomon bicolor (Mollusca: Bivalvia) on pipeline monobuoys in the Brazilian south coast

Abstract: Background: The introduction of alien species in a system affecting native species due to competition for food and space. The purse oyster Isognomon bicolor (Bivalvia, Pteriidae), a potential exotic invader, presents gaps in its distribution and ecology knowledge in Brazilian coast. For this reason, our objective was to investigate the occurrence of this oyster on pipeline monobuoys in Rio Grande do Sul, southern Brazil. Specimens were collected monthly during surveys carried out from March 2010 to June 2011 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…However, there is still no consensus on the main factors that can affect invertebrate colonization on biological substrates such as shells, carapaces, and bones. However, the surface texture has frequently been cited [ 25 31 ] together with biological factors, such as competition by recourses [ 32 , 33 ], conspecific presence [ 34 , 35 ], and ecological inter-specific interactions [ 11 , 36 ], to induce or repulse settlement. Experimental arrays conducted on non-biological hard substrates such as steel and concrete have demonstrated that invertebrate settlement might be positively [ 37 39 ] or negatively [ 39 41 ] influenced by bacterial biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still no consensus on the main factors that can affect invertebrate colonization on biological substrates such as shells, carapaces, and bones. However, the surface texture has frequently been cited [ 25 31 ] together with biological factors, such as competition by recourses [ 32 , 33 ], conspecific presence [ 34 , 35 ], and ecological inter-specific interactions [ 11 , 36 ], to induce or repulse settlement. Experimental arrays conducted on non-biological hard substrates such as steel and concrete have demonstrated that invertebrate settlement might be positively [ 37 39 ] or negatively [ 39 41 ] influenced by bacterial biofilm.…”
Section: Introductionmentioning
confidence: 99%
“…CARACTERIZAÇÃO DA MACROFAUNA DE SUBSTRATOS CONSOLIDADOS DO LITORAL NORTE DO RIO GRANDE DO SUL, BRASIL Tabela II -Espécies observadas por Rios et al (1979) Quanto ao bivalve I. bicolor, Agostini & Ozorio (2016) destacam que se trata de registro novo, o qual amplia a distribuição desta espécie exótica no litoral brasileiro. Segundo as autoras, a presença deste molusco nas monoboias de oleodutos de Tramandaí se deve a dispersão por água de lastro devido ao fluxo constante de navios no local.…”
Section: Distribuição Da Fauna Observada Nos Substratos Consolidadosunclassified